Spätantike Fabeln: Avian und Romulus lateinisch - deutsch - Avianus ca. 4./5. Jh; Romulus ca. 4./5. Jh (De Gruyter, 2022)
This volume supplements Phaedrus, Babrius, and Aesop to create a complete edition of ancient fable collections. Avian, who turned short fables into Ovidian elegiac tales, was very popular in the Middle Ages. As the 'Aesopus Latinus,' Romulus wrote the classic fables of the early modern period, and the 1476/77 edition of his works achieved world renown, from Mexico to Japan. Both authors appear here in Latin-German translation for the first time
Keywords: Avianus -- ca. 4./5. Jh.; Avian; Fabel; Literatur der Spätantike; Romulus; LITERARY CRITICISM / Ancient & Classical; Latein; Anthologie